URGENSI TAHFIZUL QURA’AN DENGAN TARTIL BAGI SANTRI PONDOK PESANTREN BAYTUL MUKKARAMAH WELALANGE KAB. BONE: URGENSI TAHFIZUL QURA’AN DENGAN TARTIL BAGI SANTRI PONDOK PESANTREN BAYTUL MUKKARAMAH WELALANGE KAB. BONE - bin Junaid, Junaid; Abdul Hakim; Andi Pemuda Muslim Putra Bangsa (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
The Qur'an will be very easy to memorize when someone believes that they can memorize it and always thinks positively. This is a motivation formed by a person's subconscious to always be motivated to memorize the Qur'an. And this belief leads someone to think that memorizing the Qur'an is easy. Before memorizing the Qur'an, intention is the most important thing. Because with intention, a person's actions can be accepted by Allah SWT. In memorizing the Qur'an, a person also needs a target to achieve an indicator of success in memorizing. Usually the target is set according to a person's ability to memorize. With a straight intention and a sincere heart because of Allah, tiredness, laziness, and feelings of difficulty will not be obstacles in memorizing the Qur'an. The method is by reading it repeatedly and many times, then after memorizing it by closing the mushaf. In addition, there is another method by reading and memorizing it line by line. By reading repeatedly like this, the verses in the Qur'an will stick in a person's head and are easy to memorize. Continuous tartil and murajaah activities can provide strength to memorization. Continuous murajaah is very urgent in memorization activities. Continuous murajaah is basically the core of memorization activities. The tartil and murojaah approach is an advantage and breakthrough in teaching the Qur'an carried out by ustad or ustadzah in the Baytul Mukarramah Islamic boarding school environment. The results of this study show that there are Tahfidzul Qur'an activities of students who use the tartil and murojaah methods to facilitate their skills in memorizing the Qur'an. All of this is done by students in an effort to support the tahfidz program at the Baytul Mukarramah Islamic boarding school located in Welalange, Bone Regency. Keywords: Urgency of Memorizing, Tahfidzul Qur'an, Tartil Qur'an.